Four-Dimensional Printing of Alternate-Actuated Composite Structures for Reversible Deformation under Continuous Reciprocation Loading - Chu, Guanghao; Zhou, Bin; Shao, Guangbin; Zhang, Dianjin; Li, Longqiu (Frontiers in Materials, 2021)
Four-dimensional (4D) printed structures are usually designed with reduced stiffness to enlarge the deformation response and weaken the loading capacity in actuated states. These actuators are suitable for non-persistent loads, such as is involved in grabbing action by a 4D printed claw. However, reduced stiffness cannot support continuous external loads during actuation. To tackle the trade-off between deformation and loading capacity, we propose herein a design using alternate actuation to attain competent loading capacity in different deformed states. In this alternate design, each unit consists of two actuated components featuring the same deformation but reciprocal stiffness, which provides the overall structural stiffness required to attain competent loading capacity during the entire deformation process. The two components are programmed to have the deformation behavior and are stimulated by thermal-expansion mismatch between polylactic acid (PLA) and carbon-fiber-reinforced PLA. An actuator featuring alternate components was designed and 4D printed to contrast its loading capacity with that of the traditional design. Experiments demonstrate a significantly improved loading capacity during actuation. This work thus provides a designing strategy for 4D printed actuators to retain competent loading capacity during the entire deformation process, which may open promising routes for applications with continuous external loads, such as 4D printed robotic arms, walking robots, and deformable wheels.